Prespektif Pendidikan Karakter Siswa Pada Sekolah Dasar Negeri 1 Taji Dan Madrasah Ibtidaiyah Muhammadiyah Gumantar Juwiring Kabupaten Klaten - Arbety Wulantika; Sukari (4, 2024)
Success in the character formation process leads children to achieve a desired goal, resulting in character formation from the strategies used in character education. The aim of this research is to determine the implementation of character education in the learning process and extracurricular activities and the evaluation model for character education in Muhammadiyah Elementary Schools and Madrasah Ibtidaiyah in Juwiring District, Klaten Regency. This research was conducted with a field study using qualitative descriptive methods. Data collection techniques are carried out through interviews, observation and documentation. The results of the research show that regarding the implementation of character education in learning, the two institutions both implement it by integrating the indicators and learning objectives of each subject. Then, to implement character education in extracurricular activities, MIM Gumantar Juwiring Klaten places greater emphasis on honesty and discipline. Evaluation of character education at MIM Gumantar Juwiring Klaten and SDN 1 Taji Juwiring Klaten uses an integrated model of indicators of achievement of learning outcomes in each subject. From the indicators of achievement of learning outcomes, it is hoped that the character values ​​developed at the two educational institutions will be able to reflect the students' personalities as superior people. The core character values ​​developed at MIM Gumantar Juwiring Klaten and SDN 1 Taji Juwiring Klaten have several differences, namely MIM Gumantar Juwiring Klaten applies the character values ​​of religious, honest, disciplined, independent, love of the homeland, respect for achievement, love of peace, and care for the environment. Meanwhile, the core character values ​​developed at SDN 1 Taji Juwiring Klaten are honesty, discipline, hard work, love of the country, respect for achievement, love of peace, social care. Abstrak Keberhasilan dalam proses pembentukan karakter mengantarkan anak untuk mencapai suatu tujuan yang diharapkan, sehingga dalam pembentukan karakter dari strategi yang digunakan dalam Pendidikan karakter. Tujuan penelitian ini untuk mengetahui implementasi pendidikan karakter dalam proses pembelajaran dan kegiatan ekstrakurikuler dan model evaluasi pendidikan karakter di Sekolah Dasar dan Madrasah Ibtidaiyah Muhammadiyah di Kecamatan Juwiring Kabupaten Klaten. Penelitian ini dilakukan dengan studi lapangan yang menggunakan metode deskriptif kualitatif. Teknik pengumpulan data dilakukan melalui wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan adapun implementasi pendidikan karakter pada pembelajaran, kedua lembaga tersebut sama-sama menerapkannya dengan cara mengintegrasikan pada indikator dan tujuan pembelajaran masing-masing mata pelajaran. Kemudian untuk implementasi pendidikan karakter pada kegiatan ekstrakurikuler, MIM Gumantar Juwiring Klaten lebih menekankan sikap religius dan peduli lingkungan, sedangkan SDN 1 Taji Juwiring Klaten lebih menekankan pada sikap jujur dan disiplin. Evaluasi pendidikan karakter di MIM Gumantar Juwiring Klaten dan SDN 1 Taji Juwiring Klaten menggunakan model terintegrasi pada indikator pencapaian hasil belajar pada masing-masing mata pelajaran. Dari indikator pencapaian hasil belajar tersebut, diharapkan nilai-nilai karakter yang dikembangkan pada kedua lembaga pendidikan tersebut mampu mencerminkan pribadi peserta didik sebagai insan yang unggul. Nilai karakter inti yang dikembangkan di MIM Gumantar Juwiring Klaten dan SDN 1 Taji Juwiring Klaten memiliki beberapa perbedaan, yakni MIM Gumantar Juwiring Klaten menerapkan nilai karakter religius, jujur, disiplin, mandiri, cinta tanah air, menghargai prestasi, cinta damai, dan peduli lingkungan. Sedangkan nilai karakter inti yang dikembangkan di SDN 1 Taji Juwiring Klaten adalah jujur, disiplin, kerja keras, cinta tanah air, menghargai prestasi, cinta damai, peduli sosial.